The use of medicinal plant resources in retirolândia, state of Bahia, Brazil - Medeiros Costa-Neto, Eraldo; Moraes Oliveira, Maria Vanilda; de Oliveira, Reyjane Patrícia; Freitas Pinheiro, Christiane (Actualidades Biológicas, 2017)
The present study attempts to record the medicinal use of 71 plants in the county of Retirolândia, State of Bahia, Northeastern Brazil. Data were obtained through open-ended interviews conducted with locals from march to june, 1997. Data showed that many of the utilized taxa are cultivated species. Plant species belonged to 41 different families, with Lamiaceae, Euphorbiaceae, Caesalpiniaceae, and Asteraceae, being the most representative ones. Plant-based remedies are prescribed for curing numerous aliments, being generally administered as teas. Pharmacological studies are needed in order to obtain information on the bioactivity of the plants and on the reliability of the medicinal properties attributed by folk tradition.